Analysis of Factors that Influence Nurse's Work Stress at the Inpatient Room of General Hospital Regional Doctor Zubir Mahmud Regency of East Aceh - Muhammad Amin; Ismail Efendy; Tri Niswati Utami (Newinera Publisher, 2022)
Work stress is a widespread issue that often affects or is complained about by employees in several nations. Consequently, the purpose of this research was to analyze the elements that impact the job stress of nurses in the inpatient room at the Regional General Hospital of Doctor Zubir Mahmud, East Aceh Regency. The research design used is a cross-sectional, analytical survey. The population for this research consisted of 129 respondents, and the sample size for the purposive sampling approach was 56 respondents. Using a simple occupational stress questionnaire, data were obtained. Analysis of data using the chi-square test. Workload had a p-value of 0.004, career uncertainty had a p-value of 0.031, and dual roles had a p-value of 0.045, indicating that it affects the job stress of nurses in the inpatient room of the Regional General Hospital Doctor Zubir Mahmud Regency. Eastern Aceh The workload variable has the biggest impact on the job stress of nurses in the hospital, as measured by the value of Exp (B) or the Odds Ratio of 19,222. This research concludes that workload, career ambiguity, and numerous jobs have an effect on the work stress of nurses in the inpatient unit of the Regional General Hospital of Doctor Zubir Mahmud in East Aceh Regency. Researchers recommend that hospitals conduct good communication routinely before work to define duties and responsibilities, give social support, enhance the abilities of nurses to adapt to current changes, and assess the ability of nurses to deal with stress.